Common School Health Problems Among School-going Adolescents in A Rural Area of Bangladesh - Asgar, Nilufar; Kabir, Md Humayun; Jeby, Dil Afroz; Shumi, Mahmuda Nasrin; Islam, Md Khalequl (Community Based Medical Journal, 2025)
School health is the comprehensive efforts of developing, implementing, and evaluating services, both within the school and the community, that provide each student with the resources needed to thrive within a healthful environment. A cross-sectional, descriptive study was conducted among 125 school-going adolescents to observe the common school health problems in a selected rural area of Bangladesh. This study was done in Aftabuddin High School and College, Bhagalpur at Bajitpur upazila under Kishoreganj district, between October and December of 2019. A purposive type of nonprobability sampling method was adopted. For collection of required data, face-to-face interview using a semi-structured questionnaire. Out of the 125 respondents, mostly 91(73%) adolescents belonged to the age group of 13-15 years and mostly 88(70%) were male. Among all respondents, 50(40%) were from class-X, followed by 28(22%) from class-VIII, 41(33%) from class-IX and rest 6(5%) from class -XI. The majority of the students 43(34.4%) suffered from dental carries in the last six months, while 21(16.8%), 7(5.6%), 6(5.2%), 11(8.8%), 10(8%) mentioned about diarrhoea, chicken pox, conjunctivitis, and respiratory infections respectively. Regarding skin problems, 23(18.4%) had head lice (pediculosis), and 12(9.6%) had ringworm and 7(5.6%) had scabies. Among eye problems, 26(20.8%) reported short sightedness (myopia), 5(4%) mentioned having hypermetropia and 4(3.2%) had squint. Regarding ear problems, 11(8.8%) had earache, 4(3.2%) reported discharge from ears and 4(3.2%) had difficulty in hearing. Among injury incidents, 25(20%) had fall from height, 2(1.6%) reported acid/alkali burn and 6(4.8%) mentioned about injuries due to fighting with friends. Among mental health issues, 54(43.2%) students reported difficulties to continue studies, while 12(9.6%) and 3(2.4%) mentioned about negligence of parents and of teachers respectively. 7(5.6%) students mentioned about physical assault by teachers or classmates and 6(4.8%) mentioned about experienced other situations like indulge in smoking/bad behaviour. Among bad habits, 17(13.6%) mentioned about their thumb sucking and 31(24.8%) had nail biting. Among the respondents, 122(97.6%) students had intentions to participate in any education/campaign related to school health problems and 3(2.4%) declined. CBMJ 2025 July: vol. 14 no. 02 P:66-70